Juridical Review of Criminal Acts of Sexual Abuse of Children Committed by TNI Officers: Study of Decision No. 88-K/PMT-BDG/AL/X/2024 - Sigar P. Berutu; Essilver Saragih; Yolani Margareta (Ekasakti Journal of Law and Justice, 2026)
This study aims to juridically analyze the criminal act of sexual abuse against children committed by Indonesian National Army officers and assess the application of the principle of the rule of law in military justice based on Decision Number 88-K/PMT-BDG/AL/X/2024. The research method used is normative legal research with a legislative approach and a case approach, using secondary data obtained through literature studies and analysis of court decisions, then analyzed qualitatively. The results of the study showed that the perpetrator's actions had fulfilled the elements of criminal offenses, namely sexual acts, intentional elements, and physical, psychological, and moral losses experienced by child victims. The military court's decision in the case reflects the application of the principle of the rule of law and equality before the law because the perpetrators are still processed and sentenced to death without any special treatment despite their status as state officials. However, there are still weaknesses in the aspect of victim protection, especially related to psychological recovery and transparency of the military justice process. Therefore, it is necessary to strengthen child protection mechanisms, increase the accountability of military law enforcement officials, and more firm and consistent law enforcement to ensure justice and legal certainty.